2018
DOI: 10.1021/acs.inorgchem.8b00281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gadolinium Scandate from a Hydroxide Hydrogel

Abstract: Gadolinium scandate (GdScO) has been synthesized at 300 °C through the decomposition of a mixed cation hydroxide hydrogel in a humid environment. Increasing the reaction temperature produced larger particles that better adopted the Wulff shape. A lack of water vapor during the synthesis caused the solid network of the hydrogel to collapse upon heating so an amorphous xerogel was produced. Water vapor in the system imbibed the hydrogel and allowed for greater diffusion of the atomic species to allow for crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…These values are in agreement with previously reported values , and help explain the large charging: the band gap and work function of DyScO 3 are approximately equal, so almost every secondary electron produced by inelastic scattering in the bulk has sufficient energy to escape the material. As a direct confirmation of this hypothesis, Figure compares secondary electron images of GdScO 3 and KTaO 3 nanoparticles. , As can be seen in this image, the GdScO 3 nanoparticles have less topographic contrast than the KTaO 3 nanoparticles, and a significantly lower secondary electron signal except near the conducting carbon support or KTaO 3 nanoparticles. The lack of topographic contrast directly indicates a long mean free path of the electrons; the lower secondary electron signal is because the GdScO 3 has charged significantly more positive than the KTaO 3.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…These values are in agreement with previously reported values , and help explain the large charging: the band gap and work function of DyScO 3 are approximately equal, so almost every secondary electron produced by inelastic scattering in the bulk has sufficient energy to escape the material. As a direct confirmation of this hypothesis, Figure compares secondary electron images of GdScO 3 and KTaO 3 nanoparticles. , As can be seen in this image, the GdScO 3 nanoparticles have less topographic contrast than the KTaO 3 nanoparticles, and a significantly lower secondary electron signal except near the conducting carbon support or KTaO 3 nanoparticles. The lack of topographic contrast directly indicates a long mean free path of the electrons; the lower secondary electron signal is because the GdScO 3 has charged significantly more positive than the KTaO 3.…”
mentioning
confidence: 54%
“…As a direct confirmation of this hypothesis, Figure 3 compares secondary electron images of GdScO 3 and KTaO 3 nanoparticles. 38,39 As can be seen in this image, the GdScO 3 nanoparticles have less topographic contrast than the KTaO 3 nanoparticles, and a significantly lower secondary electron signal except near the conducting carbon support or KTaO 3 nanoparticles. The lack of topographic contrast directly indicates a long mean free path of the electrons; the lower secondary electron signal is because the GdScO 3 has charged significantly more positive than the KTaO 3.…”
mentioning
confidence: 70%
“…Our previous report [50] on the formation of crystalline GdScO 3 from a mixed-cation hydroxide hydrogel in a water vapor-assisted reaction [51] noted the role that the humid conditions played in both preserving an open gel matrix and providing the necessary diffusion for the reactions that produced the perovskite, as insufficient diffusion instead produced an amorphous xerogel. Based on the observed products, there were two competing reactions at play:…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that high surface area GdScO 3 particles could be produced at 300 • C through the decomposition of a mixed-cation hydroxide hydrogel in a humid environment within a sealed autoclave [50], but the method was not able to produce particles with a controlled size, surface structure, or morphology. The intention of this note is to provide specific information on a two-step approach where we have successfully exploited nucleation and growth to produce well-faceted particles of rare-earth scandates by first using a higher temperature in a furnace with better control of the humidity to nucleate the relevant oxide, then a lower temperature to control step-flow growth to smooth the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The model may be used to inform synthesis design for producing smooth, well-faceted, and shape-controlled nanoparticles. In work to be published, efforts to produce wellfaceted LnScO 3 nanoparticles have been facilitated by introducing to a previously developed synthesis 48 an initial growth step in the terracing regime at higher temperature, followed by a second growth step in the smoothing regime at lower temperature. 49 This sequence has successfully formed smooth and well-faceted LnScO 3 nanoparticles, which were previously unachievable in a single heating sequence (Figure S7).…”
Section: Nano Lettersmentioning
confidence: 99%